CONSTRUCTING IDENTITY AND CONTINUING PROFESSIONAL DEVELOPMENT: A SUCCESSFUL EFL IN-SERVICE TEACHER’S STORY - Vika Anisa Gusndilla; Ista Maharsi (IAIN Syekh Nurjati Cirebon, 2022)
This research aims to reflect stories of an EFL in-service teacher (Ms. Camelia, pseudonym) about her teacher professional development experience. Assigned in a secondary school with limited facilities in a small town, she has proven to excel in her professional development and get the ultimate appreciation of an award from the Ministry of Education in 2019. Nine year-teaching experiences enriched with dozens of workshops, seminars, and being an invited guest speaker in prestigious academic forums has considerably made her an outstanding teacher. This study explores stories of her career and struggle towards crafting her identities. Data were collected from in-depth interviews and documents. The interviews were transcribed verbatim, themes and sub-themes were generated following the Interpretative Phenomenological Analysis (Smith and Osborn, 2003).Â This study finds that professional development requires high commitment on self-development, attitudes, competency, and sustaining drives. Filled with varied emotional moments, Ms. Camelia has succeeded in embracing the persistence and keeping the awareness that propel her get through signified turning points of her professional development. Those commitment and emotional aspects have built Ms. Cameliaâ€™s self-actualization towards high achievement and recognition in teaching field.